Investigating the Trip of a Transformer in Sweden During the 24 April 2023 Storm - A. P. Dimmock; V. Lanabere; A. Johlander; L. Rosenqvist; E. Yordanova; S. Buchert; S. Molenkamp; J. Setréus (Space Weather)
Abstract Geomagnetically Induced Currents are unwanted currents that flow in large ground‐based conductive infrastructure and are a significant threat to bulk power grids. This susceptibility is increased at high latitudes due to the larger amplitude geomagnetic disturbances caused by the strong and dynamic auroral electrojet currents. In Sweden, there has been a record of disturbances connected to geomagnetically induced currents; the most documented was a blackout in Malmö, a city in southern Sweden, on 30 October 2003. However, on 24 April 2023, there was a transformer trip in the Bandsjö substation (near Sundsvall) around the time of enhanced space weather. In this paper, we investigate this event by studying the solar wind properties as well as geomagnetic disturbances. The study shows evidence that the transformer trip was caused by a strong geomagnetic disturbance in the morning sector. This was triggered by a high‐pressure sub‐structure within the interplanetary coronal mass ejection cloud, preceded by 2 hr of strong southward interplanetary magnetic field. Additionally, analysis of multiple ground magnetometers shows that the geomagnetic impact was highly spatially structured.